How and Why Do Terrorist Organizations Use the Internet? - Karolina Wojtasik (Polish Political Science Yearbook, 2017)
The article gives general characterisation of the ways in which these organizations use modern communication technologies. Currently, every major terrorist organisation maintain robust media wings, which focus on producing videos, publishing magazines and sharing them with the public via the Web. The empirical system of reference is based on the activity of al-Qaeda, her franchise AQAP (al-Qaeda in the Arabian Peninsula) and ISIS (the so-called Islamic State). While analysing the media of terrorist organisations, the Lasswell model was applied. This formula is a standard research procedure used for investigating acts of communication by answering the questions: who, says what, in which channel, to whom, with what effect?. The author also present typology of videos produced by jihadist organisations, characterised the most important and active media actions of terrorist organisations and a typology of recipients of such messages. The article presents a number of reasons why the Internet has become such an important tool for terrorists.